Molecular phylogenetic analyses of albuminoids reveal the molecular evolution of allosteric properties. Issue 6 (9th April 2013) - Ascenzi, Paolo; di Masi, Alessandra; Leboffe, Loris; Alberio, Tiziana; Fanali, Gabriella; Fasano, Mauro
Abstract Serum albumin, α‐fetoprotein, afamin (also named α‐albumin and vitamin E binding protein), and vitamin D binding protein are members of the albuminoid superfamily. Albuminoids are plasma proteins characterized by a marked ability for ligand binding and transport. Here, a focused phylogenetic analysis of sequence evolution by maximum likelihood of fatty acid binding sites FA1–FA7 of mammalian albuminoids reveals that the FA1, FA2, and FA3+FA4 sites in serum albumins have evolved from the most recent common ancestor through an intermediate that has originated the α‐fetoprotein and afamin clades. The same topology has been observed for the whole protein sequences, for the sequences of all the fatty acid binding sites (FA1–FA7) taken together, and for the allosteric core corresponding to residues 1–303 of human serum albumin. The quantitative divergence analysis indicates that the ligand binding cleft corresponding to the FA2 site could be the main determinant of allosteric properties of serum albumins only. In fact, this binding cleft is structurally not effective in vitamin D binding proteins, whereas key residues that serve to allocate the allosteric effectors are not present in afamins and α‐fetoproteins. © 2013 IUBMB Life, 65(6):544–549, 2013